1980
DOI: 10.1007/bf00584183
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory action of Ca2+ on spontaneous transmitter release at motor nerve terminals in a high K+ solution

Abstract: The inhibitory effect of a high external Ca2+ ([Ca2+]o) on spontaneous transmitter release in a high K+ solution (Gage and Quastel 1966; Birks et al. 1968) was studied at the frog neuromuscular junction, based on the hypothesis that an increased intracellular free Ca2+ ([Ca2+]i) in the nerve terminal plays a key role in the depression. Three procedures were employed to increase [Ca2+]i; increasing [Ca2+]o, application of caffeine and tetanic nerve stimulation. All of these procedures increased m.e.p.p. frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…In contrast, when Ψ m was depolarized (filled circles), asynchronous release rose to much higher levels during stimulation, reaching a peak and then declining somewhat towards the end of the train. Such reductions in asynchronous release under conditions expected to elevate cytosolic [Ca 2+ ] to very high levels have also been reported by Ohta & Kuba (1980) and Calupca et al . (2001).…”
Section: Resultssupporting
confidence: 82%
“…In contrast, when Ψ m was depolarized (filled circles), asynchronous release rose to much higher levels during stimulation, reaching a peak and then declining somewhat towards the end of the train. Such reductions in asynchronous release under conditions expected to elevate cytosolic [Ca 2+ ] to very high levels have also been reported by Ohta & Kuba (1980) and Calupca et al . (2001).…”
Section: Resultssupporting
confidence: 82%
“…The same sort of question hangs over the idea that hypertonic and hypotonic solutions act by changing [Ca2+], (Shimoni, Alnaes & Rahamimoff, 1977). Moreover there is some evidence that an over-all rise in [Ca2+], can decrease the probability of release (Ohta & Kuba, 1980; Van der Kloot & Latta, in preparation), and that release at the squid synapse falls when [Ca2+], is still high (Miledi & Parker, 1981). Perhaps these uncertainties can be resolved by the use of intracellular Ca2+ buffers (Tsien, 1981 …”
Section: Methodsmentioning
confidence: 99%
“…The evidence, however, for the involvement of CICR in exocytosis at presynaptic terminals is rather indirect. Caffeine and theophylline, activators of ryanodine receptor, have been known to enhance both the evoked and spontaneous release of transmitters in several types of terminals, including frog motor nerve terminals ( Elmqvist and Feldman, 1965 ; Onodera, 1973 ; Ohta and Kuba, 1980 ; Lockerbie and Gordon-Weeks, 1986 ; Tóth et al, 1990 ). Recent studies suggested ryanodine-sensitive components of tetanus-induced rise in [Ca 2+ ] i and transmitter release in autonomic nerve terminals ( Peng, 1996 ; Smith and Cunnane, 1996 ).…”
Section: Introductionmentioning
confidence: 99%